Interactions of agents in performance based supply chain management - ÖZTEMEL, ERCAN (SPRINGER, 2009)
To acquire a competitive advantage in the expanding market, manufacturing companies should be able to manage their supply chain as much effective as possible. Measuring the supply chain performance is one of the main indicators of business success. Supply chain management (SCM) involves managing the flow of materials from suppliers to manufacturing units. This paper proposes a SCM model with performance measurement capabilities. The model is designed in such a way that it well suits to multi agent systems and related implementations. This paper highlights the components of the model especially pointing out the key parameters of performance indicators.
Keywords: Performance measurement; Supply chain management; Agent; FRAMEWORK; NEGOTIATION; NETWORK; SYSTEM